Speckle interferometry single-shot applications with multiple carrier-fringe information (2023)
The need for robust equipment that allows identifying defects or measuring small displacements in a harsh environment has been a requirement in the aeronautical and principally in the Oil & Gas industry. In this field, Digital Speckle Pattern Interferometry and shearography had been the optical techniques more used. Recently, advances in the process of phase images through multiple carrier frequencies had allowed compact optical configurations that can combine multiple acquisitions or even multiple techniques in an simple process of capture. This article shows the different applications, versatility, and compactness of the use of carrier frequencies through the multiple aperture principle.